An expedited approach for sustained delivery of bone morphogenetic protein‐7 to bone defects using gene activated fragments of subcutaneous fat. (August 2016) - Betz, Volker M.; Betz, Oliver B.; Rosin, Tom; Keller, Alexander; Thirion, Christian; Salomon, Michael; Manthey, Suzanne; Augat, Peter; Jansson, Volkmar; Müller, Peter E.; Rammelt, Stefan; Zwipp, Hans
Abstract: Background: Delivery of bone morphogenetic protein‐7 (BMP‐7) to bone defects can be improved by applying gene transfer methods. However, traditional ex vivo gene therapy approaches are cumbersome and costly, requiring the extraction and culturing of cells. Therefore, we evaluated a novel, expedited ex vivo BMP‐7 gene transfer technology based on the use of fragments of subcutaneous fat tissue. Methods: We created 5‐mm mid‐femoral bone defects in the right femora of 23 male, syngeneic Fischer 344 rats. Adipose tissue was harvested from the subcutaneous fat depot of two donor rats. Bone defects were treated with either unmodified fat (control group) or adenovirally BMP‐7 transduced fat fragments (treatment group). Healing of bone defects was assessed by radiographs, microcomputed tomography (μCT) and histology at 6 weeks after the implantation of fat tissue fragments. Results: Radiographs, μCT‐imaging and histology revealed relevant bone formation in six out of 10 rats treated with BMP‐7 activated fat grafts. Two of the defects were bridged. By contrast, femora of the control group receiving unmodified fat did not display signs of osseous healing. BMP‐7 gene activated fat treatment led to a significantly higher bone volume (11.18 ± 9.48 mm 3 ) than treatment with unmodified fat grafts (3.19 ± 1.68 mm 3 ) ( p = 0.008). Conclusions: Implantation of BMP‐7 gene activated fat tissue fragments can elicit regeneration of large bone defects in rats and could become a clinically expeditious strategy for in vivo bone tissue engineering. However, gene expression must be improved in order to reliably induce osseous bridging of critical‐size bone defects. Copyright © 2016 John Wiley & Sons, Ltd.